2021
DOI: 10.51544/jkmlh.v6i1.1962
|View full text |Cite
|
Sign up to set email alerts
|

Kecemasan Ibu Hamil Tentang Pelayanan Antenatal Care Di Era Pandemi Covid-19

Abstract: The provision of maternal services during the pandemic needs to be a concern to avoid an increase in maternal morbidity and mortality, especially at this time there are restrictions on maternal health services in the form of anxiety during pregnancy during the Covid19 pandemic. The type of research used in this study is descriptive which aims to determine the anxiety of pregnant women about ante natal care services in the era of the Covid-19 pandemic at the Bandar Khalipah Health Center in 2020. The population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
1
5
0
4
Order By: Relevance
“…Anxiety is the most common emotional problem in pregnancy. The majority of pregnant women experience mild anxiety [19] [8]. The COVID-19 pandemic has increased anxiety, but not increased rates of depression in pregnant women in Greece [20].…”
Section: Anxiety Levelmentioning
confidence: 99%
See 3 more Smart Citations
“…Anxiety is the most common emotional problem in pregnancy. The majority of pregnant women experience mild anxiety [19] [8]. The COVID-19 pandemic has increased anxiety, but not increased rates of depression in pregnant women in Greece [20].…”
Section: Anxiety Levelmentioning
confidence: 99%
“…This COVID-19 pandemic situation increases the anxiety of pregnant women, not only worrying about the condition of the fetus but also worrying about whether the mother and fetus will be healthy free of COVID-19 infection, safe or not in pregnancy checks during the pandemic [8]. The results of the study by Corbett et al (2020) in the second and third trimesters of pregnant women found that 50.7% were often worried about their health during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kondisi kehamilan sendiri dapat menyebabkan ibu hamil menjadi lebih rentan terhadap terhadap stress dan hal tersebut dapat diperparah oleh kecemasan atau kekhawatiran tertular COVID-19. Terdapat sebuah penelitian yang menunjukkan bahwa ibu hamil yang tidak khawatir tertular COVID-19 2.79 kali lebih patuh untuk memanfaatkan pelayanan kesehatan maternal termasuk ANC daripada ibu yang khawatir tertular COVID-19 (Ahorsu et al, 2020;POGI, 2020;Sianipar et al, 2021;Tadesse, 2020;Temesgen et al, 2021;W/Mariam et al, 2021).…”
unclassified